Decreasing pH of mammary gland secretions is associated with parturition and is correlated with electrolyte concentrations in prefoaling mares. (7th September 2013) - Canisso, I. F.; Ball, B. A.; Troedsson, M. H.; Silva, E. S. M.; Davolli, G. M.
Abstract : The objectives of this study were to determine pH of the mammary gland secretions and the corresponding electrolyte concentrations in prefoaling mares. Pregnant mares (seven primiparous and seven multiparous) were monitored daily from 310–320 days of gestation until parturition. Prefoaling mammary gland secretions were collected, and pH was immediately determined with a pH meter and pH strip test. An aliquot of prefoaling mammary secretions was frozen and stored until further analyses. After parturition, samples from day −4 to 0 (day of foaling) were thawed and electrolyte concentrations (ie, Ca 2 +, Mg 2 +, Na +, K + and Cl − ) were determined with an automated analyser. Data were analysed via a mixed model with the mare as a random effect. Correlations were determined between pH and electrolyte concentrations by the Pearson product‐moment for each pair. There was significant reduction in pH of mammary secretions on the day of foaling (P<0.0001), and most mares (11/14) with a pH ≤7 foaled within 24 hours. There was high correlation between the two pH methods (r=0.93). Additionally, there were significant (P<0.05) increases in Ca 2+ and K + concentrations, and significant decreases in Na + and Cl − concentrations from one day before to the day of foaling. The pH of mammary secretions was highly and significantly (P<0.001) correlated with Na + (r=0.87), Cl − (r=0.85), Ca 2+ (r=−0.88); and K + (r=−0.80) concentrations, and moderately correlated with Mg 2+ (r=−0.58). Daily evening pH measure of the mammary gland secretions can predict foaling in most mares.